Association between physical activity and the expression of mediators of inflammation in normal breast tissue among premenopausal and postmenopausal women. (February 2018) - Hanna, Mirette; Dumas, Isabelle; Orain, Michèle; Jacob, Simon; Têtu, Bernard; Diorio, Caroline
Abstract: Physical activity is associated with decreased breast cancer risk. The underlying biological mechanisms could include the reduction of the local inflammation in the breast tissue. We conducted a cross-sectional study to assess the association between the physical activity and the protein expression levels of eleven mediators of inflammation in normal breast tissue of 164 women having breast cancer. Information on total physical activity (household, occupational and recreational) performed during a one-year period was collected using a questionnaire. Normal breast tissue was obtained from mastectomy blocks distant from the tumor. The expression of the mediators of inflammation in normal breast tissue was visually evaluated by immunohistochemistry. Multivariate linear regression analyses were used to assess the prevalence ratios (PR) and 95% confidence intervals (CI) for higher protein expression levels of the mediators of inflammation in normal breast tissue across quartiles of physical activity. Higher total physical activity was associated with lower expression levels of the pro-inflammatory mediator TNF-α in normal breast epithelial tissue among all (PR = 0.64, 95% CI = 0.44–0.93 for the fourth quartile; P trend  = 0.013), premenopausal (PR = 0.61, 95% CI = 0.41–0.91 for the fourth quartile; P trend  = 0.014) and postmenopausal women (PR = 0.45, 95% CI = 0.21–0.96 for the fourth quartile; P trend  = 0.022). Conversely, higher total physical activity was associated with higher expression levels of the anti-inflammatory mediator IL-10 in normal breast epithelial tissue among all (PR = 1.66, 95% CI = 0.97–2.85 for the fourth quartile; P trend  = 0.071) and postmenopausal women (PR = 4.69, 95% CI = 1.26–17.43 for the fourth quartile; P trend  = 0.010). Our findings suggest a beneficial effect of physical activity on the local inflammatory profile in the breast tissue.